Preparation and prebiotic potential of pectin oligosaccharides obtained from citrus peel pectin. (1st April 2018) - Zhang, Shanshan; Hu, Haijuan; Wang, Lufeng; Liu, Fengxia; Pan, Siyi
Highlights: Using H2 O2 under alkaline condition (pH 10) is a new method to prepare POS. POS samples are potential prebiotic candidates, especially POSH1 . POSH1 shows the highest prebiotic score for Bifidobacterium bifidum ATCC29521 (0.92). Abstract: Pectin oligosaccharide (POS) fractions were obtained by controlled chemical degradation of citrus peel pectin. By adjusting trifluoroacetic acid (TFA) concentration, three oligosaccharides were obtained, of molecular weight (Mw) range 3000–4000 Da, 2000–3000 Da and lower than 2000 Da. Varying hydrogen peroxide (H2 O2 ) concentration and reaction time produced oligosaccharides of 3000–4000 Da and 2000–3000 Da. The relative proportions of acidic monosaccharide increased from 68.58% to 89.93% (TFA) and from 63.74% to 83.26% (H2 O2 ) as the reaction conditions intensified. Prebiotic activity scores were used to quantify POS ability to promote selective growth of specific probiotics. Sample POSH1 from H2 O2 degradation showed the highest prebiotic potential with prebiotic activity score 0.41 for Lactobacillus paracasei LPC-37 and 0.92 for Bifidobacterium bifidum ATCC 29521.